Shifting development in mid-childhood: the influence of between-task interference - Cragg, Lucy; Nation, Kate (American Psychological Association, 2009)
Performance on the task-switching paradigm is greatly affected by the amount of conflict between tasks. Compared to adults, children appear to be particularly influenced by this conflict, suggesting that the ability to resolve interference between tasks improves with age. We used the task-switching paradigm to investigate how this ability develops in mid-childhood. Experiment 1 compared 5- to 8-year-olds’ and 9- to 11-year-olds’ ability to switch between decisions about the colour of an object and its shape. The 5- to 8-year-olds were slower to switch task and experienced more interference from the irrelevant task than the 9-to 11-year-olds, suggesting a developmental improvement in resolving conflict between tasks during mid-childhood. Experiment 2 explored this further, examining the influence of stimulus and response interference at different ages. This was done by separating the colour and shape dimensions of the stimulus and reducing overlap between responses. The results supported the development of conflict resolution in task-switching during mid-childhood. They also revealed that a complex interplay of factors, including the tasks used and previous experience with the task, affected children’s shifting performance.